2015
DOI: 10.1186/s13002-015-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical survey of medicinal plants used in the East Sepik province of Papua New Guinea

Abstract: BackgroundRapid modernization in the East Sepik (ES) Province of Papua New Guinea (PNG) is resulting in a decrease in individuals knowledgeable in medicinal plant use. Here we report a synthesis and comparison of traditional medicinal plant use from four ethnically distinct locations in the ES Province and furthermore compare them to two other previous reports of traditional plant use from different provinces of PNG.MethodsThis manuscript is based on an annotated combination of four Traditional Medicines (TM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 39 publications
(309 reference statements)
1
5
0
Order By: Relevance
“…The results found in this review provide further evidence supporting the theory of non-random selection of plants, in this case, of wild food plants in Brazil. Similar findings have been reported in different socioecological contexts for medicinal plants such as in Brazil [ 57 ], India [ 4 ], Papua New Guinea [ 3 ], Italy [ 58 ], Ecuador [ 59 ], Africa [ 6 ], Europe [ 60 ], Nepal [ 7 ], and South Africa [ 8 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results found in this review provide further evidence supporting the theory of non-random selection of plants, in this case, of wild food plants in Brazil. Similar findings have been reported in different socioecological contexts for medicinal plants such as in Brazil [ 57 ], India [ 4 ], Papua New Guinea [ 3 ], Italy [ 58 ], Ecuador [ 59 ], Africa [ 6 ], Europe [ 60 ], Nepal [ 7 ], and South Africa [ 8 ].…”
Section: Discussionsupporting
confidence: 82%
“…More recently, ethnobiological studies using different approaches and statistical tools have confirmed the theory that plants are not selected at random, but there are rather taxonomic biases that determine why some species are preferred over others [ 3 8 ]. There are other approaches using phylogenetic tools which also confirm this theory.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves and roots were the most used parts in the treatment of MSDs, similar to what has been found in other studies in Thailand, such as the ethnobotany of the Mien (Yao) in northern Thailand [ 46 , 47 ], and the review of all ethnomedicinal uses of plants in Thailand [ 33 ]. Leaves were reported as the most used part in several other ethnomedicinal studies of MSD treatments around the world, such as in Algeria [ 48 ], Central Africa [ 49 , 50 ], India [ 37 ], Italy [ 51 ], Kenya [ 52 ], Papua New Guinea [ 53 ], and South Africa [ 54 ]. Additionally, leaves and roots were greatly used for the treatment of MSDs in northern Pakistan [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to considering the risk of extinction, awareness of plant conservation can also be raised by increasing the useful value of the plants. So far, I. bijuga has been used as traditional medicines in various countries including Philippines, Madagascar, Vanuatu, and Papua New Guinea to treat various diseases such as rheumatism, dysentery, urinary tract infections, asthma, diabetes, ulcers, and fractures (Norscia 2006;Koch et al 2015), while in Indonesia, its bark is used as a medicine for flatulence and liver (Widodo et al 2018). These various benefits are of course related to its various chemical compounds.…”
Section: Introductionmentioning
confidence: 99%